Work Status and Related Variables in Patients with Rheumatoid Arthritis and Ankylosing Spondylitis - Hatice BODUR; Pınar BORMAN; Betül ALPER; Dilek KESKİN (Archives of Rheumatology, 2011)
Objectives: The aim of this study was to determine and compare the work status in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS) while also defining the factors related to work disability. Patients and methods: Forty-nine patients with RA (18 males, 31 females; mean age 46.6±12.6 years) and 54 patients with AS (43 males, 11 females; mean age 35.9±9.2 years) were included in the study. The demographic and disease-related variables were recorded. The Disease Activity Score 28 (DAS28) and Health Assessment Questionnaire (HAQ) were used in RA patients and the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) in AS patients, to determine disease activity and functional status. The Short Form Health Survey (SF-36), Life Satisfaction Index (LSI), Beck Depression Inventory (BDI) and Hamilton Anxiety Scale (HAS) were used to assess quality of life (QoL), life satisfaction, depression and anxiety, respectively. The work disability ratio and related factors were evaluated in both patient groups. Results: The mean age, age at onset of disease, education level and gender of the patients were different while active phase response, pain, LSI, BDI and QoL levels assessed by SF-36 were similar between the groups. Forty-six percent of AS and 22.4% of RA patients had paid employment. Twenty-three (42.5%) of AS and 16 (32.6%) of RA patients had work disability. In the AS group, the pain by visual analog scale (VAS), the Bath Ankylosing Spondylitis Radiology Index (BASRI) and Bath Ankylosing Spondylitis Metrology Index (BASMI) scores were statistically different between work disabled and non-working disabled patients while the mean age at onset of disease, pain by VAS, the HAQ and C-reactive protein values were significantly different in RA patients with and without work disability. The HAQ and BASMI were found to be the most predictive factors for work disability in RA and AS groups, respectively. Conclusion: In conclusion, the results of our study indicate higher rates of work disability in RA and AS patients which was related to functional status and metrological limitations.